Renal Protective Effects of Dialium guineense Fruit Pulp on Serum Creatinine and Urea Levels in Ethanol-Induced Peptic Ulcers in Albino Rats - Elekwa, Elizabeth Amah; Aloh, Godwin Sunday; Agu, Kizito Akachukwu; Okoro-Akapndu, Elizabeth; Ogwo, Bertha (Sahel Journal of Life Sciences FUDMA, 2024)
Ethanol-induced peptic impacts various systems, such as renal function, with serum creatinine and urea as indicators of kidney dysfunction. Despite its known antioxidant and anti-inflammatory properties, Dialium guineense has not been explored for its potential to protect renal function against ulcerated conditions. This study evaluated its impact on renal function in albino rats with ethanol-induced peptic ulcers. Albino rats were divided into six groups (n=5): normal control, ulcer control, a reference group treated with omeprazole (20 mg/kg), and groups treated with Dialium guineense extract at 250 mg/kg, 500 mg/kg, and 1000 mg/kg. Additionally, five Dialium guineense fractions were administered at 250 mg/kg and 500 mg/kg Ulcer was induced using ethanol (5 ml/kg), followed by a 21-day treatment with Dialium guineense extract and omeprazole as the standard drug. Serum creatinine and urea levels were assayed biochemically. Ethanol significantly raised the serum creatinine and urea levels in the ulcer control group compared to the normal control (p < 0.05). Dialium guineense treatment led to a dose-dependent reduction, most notably at 1000 mg/kg (p < 0.05). The reduction in renal markers with Dialium guineense was comparable to omeprazole. Findings suggest that Dialium guineense fruit pulp may mitigate ethanol-induced renal dysfunction, indicating its potential renoprotective properties and highlighting a foundation for further research into its therapeutic uses for renal dysfunction associated with gastrointestinal disorders.